2020
DOI: 10.1021/acsami.0c14732
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Dodecylbenzene Sulfonate Interface Modification of Methylammonium Lead Iodide for Surface Passivation of Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) have been developed as a promising photovoltaic technology because of their excellent photovoltaic performance. However, interfacial recombination and charge carrier transport losses at the surface greatly limit the performance and stability of PSCs. In this work, the fabrication of high-quality PSCs based on methylammonium lead iodide with excellent ambient stability is reported. An anionic surfactant, sodium dodecylbenzene sulfonate (SDBS), is introduced to simultaneously passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 66 publications
(102 reference statements)
0
26
0
Order By: Relevance
“…[ 34–35 ] While the emission peak of the 4‐AMTHP‐Ac modified CsPbIBr 2 film appears at 603.3 nm, which is a redshift of 2.5 nm, indicated that the 4‐AMTHP‐Ac modified CsPbIBr 2 film shows a lower surface optical bandgap, thus allowing more light absorption from the sunlight spectrum than the pristine one. [ 36 ] Moreover, the PL peak intensity of the 4‐AMTHP‐Ac modified CsPbIBr 2 film is increased, indicating reduced nonradiative recombination and lower defect density. [ 37 ] The TRPL decay curves are fitted with a double exponential decay function, as shown in Figure 4b, and the relative parameters are listed in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34–35 ] While the emission peak of the 4‐AMTHP‐Ac modified CsPbIBr 2 film appears at 603.3 nm, which is a redshift of 2.5 nm, indicated that the 4‐AMTHP‐Ac modified CsPbIBr 2 film shows a lower surface optical bandgap, thus allowing more light absorption from the sunlight spectrum than the pristine one. [ 36 ] Moreover, the PL peak intensity of the 4‐AMTHP‐Ac modified CsPbIBr 2 film is increased, indicating reduced nonradiative recombination and lower defect density. [ 37 ] The TRPL decay curves are fitted with a double exponential decay function, as shown in Figure 4b, and the relative parameters are listed in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The fast decay component (A1) is the nonradiative recombination induced by the trap, and the slow decay component (A2) represents the radiative recombination of free carriers. [ 36 ] Compared with the pristine CsPbIBr 2 , the A1 of the 4‐AMTHP‐Ac modified CsPbIBr 2 film decreases, and the A2 increases. The average carrier lifetime also increases from 4.13 to 6.83 ns, indicating that the defects in the 4‐AMTHP‐Ac modified CsPbIBr 2 film are significantly passivated.…”
Section: Resultsmentioning
confidence: 99%
“…The power conversion efficiency (PCE) of organic-inorganic hybrid (halide) perovskite solar cells (PSCs) has rapidly progressed in the last few years, from 3.8% in 2009 to 25.5% at present. [1][2][3][4][5][6] Rapid progress has been enabled by the outstanding optoelectronic properties of these perovskites, including long charge carrier diffusion lengths, a high optical absorption coefficient, balanced electron and hole mobilities, a long photogenerated carrier lifetime, low trap density, and small exciton binding energies. [7][8][9][10][11][12][13][14][15] However, due to low formation energies, the polycrystalline perovskite films contain crystallographic defects and grain boundaries (GBs) at the interface and in the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Undergoing about 10 years of rapid development, the power conversion efficiency (PCE) of organic–inorganic hybrid perovskite solar cells (PSCs) has reached 25.5% from the initial 3.8%, which can be ascribed to the intrinsic advantages of the perovskite materials, such as high absorption coefficient, long hole/electron diffusion lengths, ideal charge mobility, adjustable band gap, etc. However, due to the polycrystalline characteristics of the perovskite film in normal PSCs, defects are readily formed at the grain boundaries and on the surface of the films, which will function as the nonradiative recombination center decreasing the device performance. Moreover, defects can accelerate the moisture-induced destruction of perovskite materials . Furthermore, the misalignment of energy levels near the interface between the perovskite/hole transport layer (HTL) in typical n-i-p PSCs will inevitably lead to recombination loss across interfaces .…”
Section: Introductionmentioning
confidence: 99%
“…37,38 The long and orderly π−π stacking structure could provide a good channel for charge transport. Inspired by this, we designed and synthesized a new porphyrin-involved dendrimer N 1 ,N 3 ,N 5 -tri(4-(10,20-di(4-dodecyloxyphenyl)porphyrin-5-yl)phenyl)-1,3,5-benzenetricarboxamide (hereafter abbreviated as Por-BTA, Figure 1a) for use as an efficient interface material between perovskite/HTM to improve the PSCs' device performance. The strong intermolecular aggregation could be achieved via the van der Waals forces induced by the dodecyloxyphenyl group at 10, 20 positions of porphyrin, along with the hydrogen-bonding interactions between the amide groups.…”
Section: Introductionmentioning
confidence: 99%